POSITIONING BALAI HARTA PENINGGALAN AS PERSONAL AND MICRO SMALL MEDIUM ENTERPRISES BANKRUPTCY ADMINISTRATOR PROFESSION IN THE DIGITAL ECONOMIC ERA - Anggoro, Teddy (Jurnal Rechts Vinding: Media Pembinaan Hukum Nasional, 2024)
Bankruptcy is a complex and expensive legal process, with the cost of administrator services being the contributors to the high cost of this process. The Balai Harta Peninggalan (BHP) as a administrator should not be a burden to the bankrupt debtor. Especially in the era of massive use of online loans which causesH individuals and MSMEs experience financial distress. This research examines the current role of BHP and how BHP positions itself in the bankruptcy of individuals and MSMEs in the digital economy era. Using the juridical-normative method, this study concludes that the role of BHP is smaller than the private administrator. However, BHP's involvement holds the key to making bankruptcy efforts inclusive for individual debtors and MSMEs. This can be done by regulating that BHP is obliged to handle the bankruptcy of individuals and MSMEs as well as bankruptcy costs supported by the state budget.